Global Health Impacts of Vector-Borne Diseases: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Pathogens transmitted among humans, animals, or plants by insects and arthropod vectors have been responsible for significant morbidity and mortality throughout recorded history. Such vector-borne diseases – including malaria, dengue, yellow fever, and plague – together accounted for more human disease and death in the 17th through early 20th centuries than all other causes combined. Over the past three decades, previously controlled vector-borne diseases have resurged or reemerged in new geographic locations, and several newly identified pathogens and vectors have triggered disease outbreaks in plants and animals, including humans. Domestic and international capabilities to detect, identify, and effectively respond to vector-borne diseases are limited. Few vaccines have been developed against vector-borne pathogens. At the same time, drug resistance has developed in vector-borne pathogens while their vectors are increasingly resistant to insecticide controls. Furthermore, the ranks of scientists trained to conduct research in key fields including medical entomology, vector ecology, and tropical medicine have dwindled, threatening prospects for addressing vector-borne diseases now and in the future. In June 2007, as these circumstances became alarmingly apparent, the Forum on Microbial Threats hosted a workshop to explore the dynamic relationships among host, pathogen(s), vector(s), and ecosystems that characterize vector-borne diseases. Revisiting this topic in September 2014, the Forum organized a workshop to examine trends and patterns in the incidence and prevalence of vector-borne diseases in an increasingly interconnected and ecologically disturbed world, as well as recent developments to meet these dynamic threats. Participants examined the emergence and global movement of vector-borne diseases, research priorities for understanding their biology and ecology, and global preparedness for and progress toward their prevention, control, and mitigation. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

The Emerging Field of Human Neural Organoids, Transplants, and Chimeras: Science, Ethics, and Governance - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Each year, tens of millions of individuals in the U.S. suffer from neurological and psychiatric disorders including neurodegenerative diseases such as Alzheimer's Disease and Parkinson's Disease, and psychiatric disorders such as autism spectrum disorder, depression and schizophrenia. Treatments for these diseases are often completely lacking or only partially effective, due in large part to the difficulty of conducting brain research and the complexity of the brain itself. Researchers in recent years have developed new models to better represent and study the human brain. The three models considered in this report, all of which generate and use pluripotent stem cells from healthy individuals and patients, are human neural organoids, human neural transplants, and human-animal neural chimeras. The Emerging Field of Human Neural Organoids, Transplants, and Chimeras: Science, Ethics, and Governance reviews the status of research, considers its benefits and risks, discusses associated ethical issues, and considers governance mechanisms for this type of research.
Keywords: Health and Medicine

Children's Environmental Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Board on Population Health and Public Health Practice, Board on Environmental Studies and Toxicology, and Board on Children Youth and Families convened a workshop in August 2022 to explore the impact of specific environmental exposures in utero, infancy, early childhood, and adolescence. Experts in epidemiology, toxicology, dose response methodology, and exposure science explored gaps in knowledge around vulnerabilities to environmental hazards as well as opportunities to inform public policy moving forward. This Proceedings of the workshop summarizes important discussions held during the virtual event and outlines recommendations for ways the Environmental Protection Agency can incorporate new research methods into its risk assessments.
Keywords: Health and Medicine; Environment and Environmental Studies

Review of the Draft Interagency Report on the Impacts of Climate Change on Human Health in the United States - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The U.S. National Climate Assessment identified a number of ways in which climate change is affecting, and is likely to affect, people, infrastructure, natural resources, and ecosystems. Those impacts, in turn, are increasingly having important current and potential future consequences for human health. There is a need to probe more deeply into how climate change impacts on the environment can create environmental stressors that, in turn, are having and/or have the potential to have significant impact on human health in a number of dimensions. In response to this need, the U.S. Global Change Research Program (USGCRP) has initiated an interagency Scientific Assessment on the Impacts of Climate Change on Human Health in the United States. The Assessment is intended to inform public health authorities, other planning and policy entities, and the general public. Review of the Draft Interagency Report on the Impacts of Climate Change on Human Health in the United States evaluates the scientific basis, findings, and key messages of the USGCRP Draft Assessment. This report offers a number of overarching suggestions on how the USGCRP report authors can enhance their identification and assessment of the science and better communicate their conclusions to all of their target audiences. These recommendations this help the Assessment to play a significant role in continued efforts to examine and explore the impacts of climate change on human health.
Keywords: Environment and Environmental Studies; Health and Medicine